Movement characteristics of volleyball spike jump performance in females - Fuchs, P. X.; Fusco, A.; Bell, J. W.; von Duvillard, S. P.; Cortis, C.; Wagner, H. (Journal of Science and Medicine in Sport, 2019)
Objectives: Performance factors in the volleyball spike jump are well known for male players; however, technical-coordinative differences for female players are known only marginally. The objective of this study was to investigate the relationship between movement characteristics and female` spike jump performance and to identify the most relevant aspects of jump height and ball velocity. Design: Single group correlation and regression. Methods: Fifteen elite female volleyball players performed spike jumps by striking a stationary ball at maximal jump height. Data were collected via twelve MX13 Vicon cameras (250 Hz), two AMTI force plates (2000 Hz), and controlled via Visual3D software. Results: Ten out of 42 characteristics correlated with jump height and none of 22 correlated with ball velocity. A stepwise regression model (adjusted R2 = 0.82, p < 0.001) predicted jump height based on orientation step length and maximal angular velocity of dominant knee extension. For ball velocity, stepwise regression analysis was not feasible; however, an alternative model yielded adjusted R2 = 0.55, p < 0.01. Conclusions: Key aspects for jump height were (1) optimised approach and energy conversion, (2) wide dynamic arm swing allowing for a forceful countermovement and, thus, increased range of motion in lower limbs, and (3) large angular velocities in ankles and knees, especially on the dominant side. These aspects strongly determined jump height in females and should be included in technical and strength-related training. For ball velocity, upper body anthropometrics and angular joint velocities emerged as the most important criteria. The importance of specific joints may depend on variations in striking technique.